2017
DOI: 10.1590/0102-311x00050916
|View full text |Cite
|
Sign up to set email alerts
|

Infecção latente por tuberculose entre pessoas com HIV/AIDS, fatores associados e progressão para doença ativa em município no Sul do Brasil

Abstract: Resumo: Propôs-se levantar a prevalência de infecção latente por tuberculose (ILTB) entre pessoas vivendo com HIV/AIDS (PVHA), fatores associados e se entre os casos identificados houve progressão para tuberculose ativa. Trata-se de estudo epidemiológico e descritivo. A população foi composta de PVHA, atendidas entre 2003 e 2014 em um centro de referência para HIV/AIDS. Os dados foram coletados com base em prontuários e fichas do Sistema de Informação de Agravos de Notificação (SINAN). Procedeu-se à estatístic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
(44 reference statements)
0
14
0
6
Order By: Relevance
“…In the study conducted by Saraceni et al 30 in Rio de Janeiro, only 17 of 67 eligible PLHIV (25.4%) had access to PTI; adherence to PTI was 53% among Brazilian patients enrolled in general healthcare facilities 31 . Santos et al 32 showed that 53 out of 66 eligible PLHIV had access to PTI (80.3%), but only 26 completed PTI (49.1%). In our own institution, a cross-sectional study conducted in 2005 showed that only 59% of eligible PLHIV had access to TST and only 55% of eligible patients had access to PTI 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Saraceni et al 30 in Rio de Janeiro, only 17 of 67 eligible PLHIV (25.4%) had access to PTI; adherence to PTI was 53% among Brazilian patients enrolled in general healthcare facilities 31 . Santos et al 32 showed that 53 out of 66 eligible PLHIV had access to PTI (80.3%), but only 26 completed PTI (49.1%). In our own institution, a cross-sectional study conducted in 2005 showed that only 59% of eligible PLHIV had access to TST and only 55% of eligible patients had access to PTI 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, TB has been one of the main factors which contributed to death in people with HIV, with a national growth of 9.8% in the incidence of TB/HIV co-infection (27) . The city of Porto Alegre has stood out for its high rates of TB/HIV co-infection.…”
Section: Descriptoresmentioning
confidence: 99%
“…In the dimension of health education, few amenities were quantified when compared to the difficulties. The literature states that when it comes to the empowerment of TB patients as a strategy for disease control, it is emphasized the importance of health education as a political act, which can promote dialogue between health professionals and users, autonomy and incentive to an active posture of these subjects in their political and social environments (Fernandes et al, 2010;Santos et al, 2017). In this aspect, it was found that:…”
Section: Lack Of Necessary Resources To Perform Educational Activities Sputum Collection Laboratory Support Difficult Access To Medicatiomentioning
confidence: 99%